The L2 learner's performance - Ali, Amina Ibrahim (School of Education, UWI, St. Augustine, 2008)
It is generally accepted that the native speaker's grammatical competence differs from his performance, as the speech act is influenced by memory limitations, distractions, and slips of the tongue. However, because this theory applies in the context of the ideal speaker-listener in a homogeneous speech community, communication is not hampered. How, therefore, can the competence of an L2 learner be measured, as he operates within an evolving system of interlanguage, that ebbs and flows to and from the target? Can it be said that the language learner "knows" a set of grammatical structures in the target language when he scores satisfactorily in a timed assessment or class activity, or is his competence characterized by what he produces on his feet, as it were, in spontaneous language production? During a 10-week semester, data were collected from 13 EFL students in the form of errors made during in-class spoken and written tasks/tests. These were measured against errors sourced from student e-mails to the teacher-a system of electronic communication requested that had no bearing on the course and was optional. It was felt that, although written, the medium was as natural as spoken language, existing as a better indicator of the language learner's competence
Keywords: Language education; Foreign languages; English as a foreign language; Error analysis; Trinidad and Tobago